1995
DOI: 10.4267/10608/2395
|View full text |Cite
|
Sign up to set email alerts
|

Activation du système de facteurs de transcription Rel/NF-κB

Abstract: R. Costello : poste d' accueil lnsenn. P. Lecine : n.llocatrâre de recl!l'rche MESR. B. Kahn-Perlès : chmgée de 1•echerrhe au Cnrs. M. Algané : al/1) w.tmre de re cherche MESR. C. Lipcey : ingé nieur à 1'/nsenn. D. Olive : directeur de recherrhe à l'Inserm. J. 1 rn bert : chargé de 1• echerche à l'fn senn. Laboratoire d'immunologie fo nction nelle el moléculaire, Inserm U. l l9, 27, bou levard Lei-Roure, 13009 Marseille, France. Voir aussi la. mini-sy nthès e d'A. lsmil, jmge 101 7 de ce numéro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

1996
1996
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 0 publications
1
17
0
2
Order By: Relevance
“…In contrast, stimulation by anti CD2 or anti CD28 mAb alone did not give rise to a measurable level of thymidine incorporation (Figure 1b), nor to an increase in cell number. Similarly, CD2+CD28 costimulation activated the secretion of IL-2 which peaked around 4 days, as well as the expression of IL2Ra chain of the receptor at the cell surface, which lasted for at least 3 weeks, with more than 80% of the cells scoring positive (data not shown, Costello et al, 1993). Medium alone, single anti CD2 or anti CD28 stimulations, were ine ective in inducing a detectable level of secreted IL-2, neither an increase of IL-2Ra chain at the cell surface (data not shown).…”
Section: Cyclin a Expression In Primary Human T Lymphocytesmentioning
confidence: 88%
“…In contrast, stimulation by anti CD2 or anti CD28 mAb alone did not give rise to a measurable level of thymidine incorporation (Figure 1b), nor to an increase in cell number. Similarly, CD2+CD28 costimulation activated the secretion of IL-2 which peaked around 4 days, as well as the expression of IL2Ra chain of the receptor at the cell surface, which lasted for at least 3 weeks, with more than 80% of the cells scoring positive (data not shown, Costello et al, 1993). Medium alone, single anti CD2 or anti CD28 stimulations, were ine ective in inducing a detectable level of secreted IL-2, neither an increase of IL-2Ra chain at the cell surface (data not shown).…”
Section: Cyclin a Expression In Primary Human T Lymphocytesmentioning
confidence: 88%
“…A similar assay with Kit225 nuclear extracts revealed that, beside a previously characterized minor Elf-1 component (Lecine et al, 1996), the C1 complex was also mainly composed of GABPa/b (data not shown). Since IL-2 secretion by CD2+CD28-stimulated T lymphocytes peaked at day 4 ± 6 (Costello et al, 1993), we focused on the DNAbinding speci®city and composition of the inducible C2p in T cells 6 days after stimulation. Competition experiments with wild-type, GAS and/or EBS disrupted oligonucleotides evidenced that C2p was speci®c for the GASd motif (Figure 6b), as reported above for IL-2-induced C2/C3 complexes in the leukemic T cell model Kit225.…”
Section: Cooperative Transcriptional Activation By Stat5b Ets-1 and mentioning
confidence: 99%
“…The cells were arrested in a quiescent state by washing them twice in PBS, and culturing in RPMI 1650 10% FCS without IL-2 for 20 h (for transient transfection assays) and for 2 days (for EMSAs, a nity puri®cation of DNA-binding proteins GST-pull down and immunoprecipitations). T cell puri®cation from human peripheral blood and activation were performed as described (Costello et al, 1993).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…T Cell Purification, Activation, and Treatments-T cell purification from peripheral blood and activation were performed as previously described (42). Primary T cells were maintained in RPMI, 10% fetal calf serum (FCS).…”
Section: Methodsmentioning
confidence: 99%